Design and development of visual learning techniques to construct chemical engineering safety knowledge - Nishaben Santibhai, Dholakiya (2009)
People working in the chemical industry require specific skills to deal with hazardous environments and to operate complicated machinery which often requires on site training. The importance of designing systems and environments with safe possible ways to train operators is essential for the chemical industries. Virtual reality offers the potential to train personnel in a safe highly visual and interactive manner.